Types of nominations in modern Kazakh short story - Saparova, Akhlima I.; Soltanayeva, Yerkingul M.; Yılmaz, Gülşah (The New Research of Tuva, 2025)
The article identifies and analyzes various types of naming in contemporary Kazakh short stories: metaphorical names, relational names, personal names, as well as sacred and mythological names. The source base of the study includes stories by writers Talasbek Asemkulov “The Old Kui Player”, Alibek Askarov “Mona Lisa”, Zhusipbek Korgasbek “Art”, and Beksultan Nurzhekeev (Nurzheke-uly) “The Death of the Soul”. It is noted that the authors use metaphorical naming based on comparisons between close individuals and culturally sacred animals, such as the horse, which holds a special place among Kazakhs and other Turkic peoples. Relational names may function as etiquette-based nominations of literary characters. This type of nomination reflects the value of close kinship ties in Kazakh culture and the respectful attitude toward outsiders. Personal names of literary characters carry semantic links to natural phenomena and often belong to a subgroup of names associated with fauna. Sacred and mythological names preserve the cultural memory of the people, reflecting their ethical, moral, and religious beliefs. These include the names of legendary ancestors, saints, and demonic entities. This category of nominations leads the reader toward religious and mythological contexts.